Funcional lead-free composite - Teixeira, G. F. [UNESP]; De Oliveira, J. A.M.; Zaghete, M. A.; Longo, E.; Varela, J. A. (My University, 2014)
In the present work we report the properties of NaNbO3 ceramic particles obtained by microwave-assisted hydrothermal method and its use in composites with PVDF polymer. Results indicated that Na2Nb 2O6.H2O particles can be used as precursor to fabricate NaNbO3 fibers-like particles. Photoluminescence spectra, shown that NaNbO3 particles has emission around 445 nm, and the composites obtained using these particles emits in 565 nm. This displacement is due to different defects presented by the composite and the particles. The P-E hysteresis loop of composite shown remanent polarization of 1.5 μC/cm 2.
Keywords: Composites; Lead-free; Microwave-assisted hydrothermal method; PVDF